Maine Forts - Henry E.Dunnack; Dunnack, Henry E.; Maine State Library (1867-1938) (Augusta, ME : Press of Charles E. Nash and Son, 1924)
Contains historical information on many Maine forts some still standing and others that have been destroyed
Maine author.
Keywords: Abenaki people; Archaeology -- Maine; Fortification -- Maine; Historic buildings -- Maine; Maine -- History; Maine -- History, Military